1995
DOI: 10.1002/jcb.240570206
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical characterization of mineralizing primary cultures of avian growth plate chondrocytes: Evidence for cellular processing of Ca2+ and Pi prior to matrix mineralization

Abstract: Advances in the culture of mineralizing growth plate chondrocytes provided an opportunity to study endochondral calcification under controlled conditions. Here we report that these cultures synthesize large amounts of proteins characteristically associated with mineralization: type II and X collagens, sulfated proteoglycans, alkaline phosphatase, and the bone-related proteins, osteonectin and osteopontin. Certain chondrocytes appeared to accumulate large amounts of Ca2+ and Pi during the mineralization process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
87
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 55 publications
7
87
0
1
Order By: Relevance
“…It was reported that both intracellular and extracellular calcium and phosphate levels increase in the hypertrophic area where terminally differentiated chondrocytes mineralize the surrounding matrix and subsequently die (11,30,33). In vitro studies have also made clear that P i induces the mineralization and cell death of chondrocytes (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that both intracellular and extracellular calcium and phosphate levels increase in the hypertrophic area where terminally differentiated chondrocytes mineralize the surrounding matrix and subsequently die (11,30,33). In vitro studies have also made clear that P i induces the mineralization and cell death of chondrocytes (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown calcium is known to have an effect on the extracellular matrix deposition of cartilage [35,43,44]. The intracellular concentration of calcium channels plays an important role in regulating chondrocyte proliferation and maturation in monolayer [44], and therefore high concentrations of calcium could be of benefit for cartilage tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Bone healing by endochondral ossification is influenced by many regulatory mechanisms. However, while interaction of Indian hedgehog (Ihh) and Parathyroid hormone related protein (PTHrP) is one of the best known regulatory mechanism in the growth plate, such an interplay is yet unknown for fracture healing (Wu, Ishikawa et al 1995;Vortkamp, Lee et al 1996;Volk and Leboy 1999). The role of growth factors during bone healing processes is better studied.…”
Section: Bone Repairmentioning
confidence: 99%